Gastrointestinal Microenvironment and the Gut-Lung Axis in the Immune Responses of Severe COVID-19 - Yang, Yun; Huang, Weishan; Fan, Yubo; Chen, Guo-Qiang (Frontiers in Molecular Biosciences, 2021)
The global pandemic of coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is an unprecedented threat to the human health. A close association of the digestive tract is implied by the high frequency of gastrointestinal syndromes among COVID-19 patients. A better understanding of the role of intestinal microenvironment in COVID-19 immunopathology will be helpful to improve the control of COVID-19 associated morbidity and mortality. This review summarizes the immune responses associated with the severity of COVID-19, the current evidence of SARS-CoV-2 intestinal tropism, and the potential involvement of gut microenvironment in COVID-19 severity. Additionally, we discuss the therapeutic potential of probiotics as an alternative medicine to prevent or alleviate severe COVID-19 outcome.